Contribution of the Academician A.A. Korzh into development of the national orthopedics, traumatology and prosthetics (to the 90th anniversary of the birth) - Yaremenko, Dmytro; Shevchenko, Stanislav (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2014)
The article outlined the main stages of life and scientific, educational, organizational and social activities of the prominent Ukrainian scientist in the field of orthopaedics, traumatology and prosthetics, an Academician of the AMS of USSR, the NAS and AMS of Ukraine and the Russian Academy of Medical Sciences, State Prize Laureate in Science and Technique, Honored Personality on Science and Technique, Doctor of medical sciences, Professor Korzh Alexey Alexandrovich who made significant contributions to the development of national and world medicine. Scientific interests of the Academician cover wide range of issues on diagnostics, treatment and prevention of diseases and injuries of the musculoskeletal system of the human beings, theoretical and practical aspects of the specialty, organization of orthopaedic and trauma service in the former Soviet Union and Ukraine, in particular, as well as personnel training and promotion of up-to-date advances.